A key general stress response motif is regulated non‐uniformly by CAMTA transcription factors. (19th August 2014) - Benn, Geoffrey; Wang, Chang‐Quan; Hicks, Derrick R.; Stein, Jeffrey; Guthrie, Cade; Dehesh, Katayoon
Summary Plants cope with environmental challenges by rapidly triggering and synchronizing mechanisms governing stress‐specific and general stress response (GSR) networks. The GSR acts rapidly and transiently in response to various stresses, but the underpinning mechanisms have remained elusive. To define GSR regulatory components we have exploited the Rapid Stress Response Element (RSRE), a previously established functional GSR motif, using Arabidopsis plants expressing a 4xRSRE::Luciferase (RSRE::LUC) reporter. Initially, we searched public microarray datasets and found an enrichment of RSRE in promoter sequences of stress genes. Next, we treated RSRE::LUC plants with wounding and a range of rapidly stress‐inducible hormones and detected a robust LUC activity solely in response to wounding. Application of two Ca2+ burst inducers, flagellin22 (flg22) and oligogalacturonic acid, activated RSRE strongly and systemically, while the Ca2+ chelator ethylene glycol tetraacetic acid (EGTA) significantly reduced wound induction of RSRE::LUC. In line with the signaling function of Ca2+ in transduction events leading to activation of RSRE, we examined the role of CALMODULIN‐BINDING TRANSCRIPTIONAL ACTIVATORs (CAMTAs) in RSRE induction. Transient expression assays displayed CAMTA3 induction of RSRE and not that of the mutated element mRSRE. Treatment of selected camta mutant lines integrated into RSRE::LUC parent plant, with wounding, flg22, and freezing, established a differential function of these CAMTAs in potentiating the activity of RSRE. Wound response studies using camta double mutants revealed a cooperative function of CAMTAs2 and 4 with CAMTA 3 in the RSRE regulation. These studies provide insights into governing components of transduction events and reveal transcriptional modules that tune the expression of a key GSR motif.